Problem-Based Learning To Improve Students’ Critical Thinking Skill - Mochamad cholik Cholik; Tri Riyanto; Ari Sriantini; Ridzwan bin Che’Rus (At-Tarbiyat, 2022)
Problem-based learning is learning by presenting contextual problems. Mechanical Engineering Subjects to support the competence and competitiveness of students majoring in Mechanical Engineering at Vocational High School. The purpose of the research is to describe the results of the application of problem-based learning in order to improve students' critical thinking skills and improve problem solving skills in mechanical engineering subjects.This research is classroom action research. The subject of this study involved students of class XI of the Mechanical Engineering Study Program at SMK Negeri 3 Bojonegoro, 32 people, in the 2021/2022 academic year. This critical thinking skill uses indicators developed by Ennis.The results of cycle 3 for good criteria are 44% and very good are 28%. The number of percentages in solving problems is 72%. The results in cycle 3 for good criteria are 44% and very good are 31%. Total percentage for critical thinking ability is 75%. This shows that both of these things have exceeded the minimum percentage set at 70%, or in other wordsThe problem-based learning process can develop students' critical thinking skills in mechanical engineering subjects in SMK.The results of the research above can be said that there is a relationship between the problem-based learning process on students' critical thinking.